Long Term Compression Strength of Mortars Produced Using Coarse Steel Slag as Aggregate - Erika Furlani; Stefano Maschio (Advances in Civil Engineering)
The paper reports on some experimental results obtained from the production of mortars prepared using a commercial cement, coarse steelmaking slag, superplasticizer, and water. The behaviour of this reference composition was compared to that of some others containing further additives in order to investigate materials compressive strength after long time ageing. It has been demonstrated that an optimized water/cement ratio coupled with slag particles of size lower than 2.5 mm and proper protocol of preparation leads to the production of materials with good mechanical properties after 28, 90, and 180 days of ageing. The resulting materials therefore appeared as good candidates for civil engineering applications. However, the present research also demonstrates that the mortar samples of all of the compositions prepared suffer from decay and compressive strength decrease after long time ageing in water. In the present paper the results are explained taking account of materials residual porosity and alkali silica reaction which occurs in the samples.